Growth in body size affects rotational performance in women's gymnastics - Acklands, T.; Elliott, B.; Richards, J. (Sports Biomechanics, 2003)
National and state representative female gymnasts (n=37), aged initially between 10 and 12 years, completed a mixed longitudinal study over 3.3. years, to investigate the effect of body size on gymnastic performance. Subjects were tested at four-month intervals on a battery of measures including structural growth, strength and gymnastic performance. The group were divided into 'high growers' and 'low growers' based on height (>18 cm or <14 cm / 37 months, respectively) for comparative purposes. Development of gymnastic performance was assessed through generic skills (front and back rotations, a twisting jump and a V-sit action) and a vertical jump for maximum height. The results show that the smaller gymnast, with a high strength to mass ratio, has greater potential for performing skills involving whole-body rotations. Larger gymnasts, while able to produce more power and greater angular momentum, could not match the performance of the smaller ones. The magnitude of growth experienced by the gymnast over this period had a varying effect on performance. While some activities were greatly influenced by rapid increases in whole-body moment of inertia (e.g. back rotation), performance on others like the front rotation and vertical jump, appeared partly immune to the physical and mechanical changes associated with growth.